Efficient synthesis of organic thioacetates in water. Issue 41 (9th October 2018) - Olivito, F.; Costanzo, P.; Di Gioia, M. L.; Nardi, M.; M., Oliverio; Procopio, A.
Abstract : A green, mild and safe synthetic procedure to obtain organic thioacetates in almost quantitative yield via aqueous nucleophilic displacement. Abstract : Thioacetates as precursors of thiols are interesting starting points for synthesizing other organosulfur compounds. Herein, we propose a simple, efficient and fast method to obtain organic thioacetates using water as a solvent. Taking into account the great attention that has been paid toward environmentally friendly synthetic procedures in the past decades, we prove the role and the strength of the thioacetate anion as a nucleophile for nucleophilic displacement reactions in an aqueous medium. The reactions were carried out under pH control, to prevent the decomposition of the mesylate starting materials, using potassium carbonate as a safe and mild base. A simple work up allows products to be obtained with excellent yield and acceptable purity.